2016
DOI: 10.1016/j.ijcard.2016.03.068
|View full text |Cite
|
Sign up to set email alerts
|

Isolated arterial calcifications of the lower extremities: A clue for NT5E mutation

Abstract: A forty-two year old man was referred to the Dept. of Vascular Medicine because of severe intermittent claudication of both legs, that started at the age of 27. He never smoked, used alcohol in moderation and didn't use illicit drugs. His medication included acetylsalicylic acid and rosuvastatin. His family history was unremarkable, notably with no atherosclerotic disease and no consanguinity. His medical history revealed pain in several small joints of the hands, knees, and ankles since 1994, without rheumato… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 4 publications
(5 reference statements)
0
7
0
Order By: Relevance
“…However, the genotype-phenotype relationship is still unknown because only a few cases have been reported. [6][7][8][9][10] Because the disease is late-onset, other factors might also contribute to the severity and timing of onset. Based on the allele frequency, there might be undiagnosed patients with the homozygous variant of NT5E.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…However, the genotype-phenotype relationship is still unknown because only a few cases have been reported. [6][7][8][9][10] Because the disease is late-onset, other factors might also contribute to the severity and timing of onset. Based on the allele frequency, there might be undiagnosed patients with the homozygous variant of NT5E.…”
Section: Discussionmentioning
confidence: 99%
“…6 Since they unveiled mutations of the NT5E (5′-ectonucleotidase) gene as a cause of CALJA, 6 14 patients from 7 families have been reported around worldwide (Table). [7][8][9][10] Heavily calcified occluded arteries of the lower extremities caused intermittent claudication (IC) as an ischemic symptom in many of these patients, but there is no literature on CALJA patients needing vascular reconstruction for limb salvage. Herein, we report 2 families with identical genetic mutation patterns, and 3 patients needed distal bypass surgeries, including 1 patient with chronic limb-threatening ischemia (CLTI) who had already lost her lower extremity before being diagnosed with CALJA.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…1 From this first description, only four other families have been described worldwide. [2][3][4][5] In vitro assays demonstrated that CD73deficient fibroblasts reduced extracellular adenosine levels and enhanced the activity of tissue non-specific alkaline phosphatase, which generates procalcifying extracellular Pi. CALJA is an adult-onset disease, with the first symptoms occurring during the second decade of life.…”
Section: Descriptionmentioning
confidence: 99%
“…1 Since then, only 14 patients from 7 families have been reported as having CALJA. [2][3][4][5] Patients with CALJA often experience ischemic symptoms in the lower extremities secondary to severely calcified and occluded arteries. CD73 is also known to play a protective role against aortic valve calcification by hydrolyzation of adenosine monophosphate (AMP) to adenosine.…”
Section: Introductionmentioning
confidence: 99%